Assessment of Serum Advanced Glycation End-Product Level and Its Effect on Periodontal Health Status in Type 2 Diabetic Patients with Chronic Periodontitis - Lara Kusrat Hussein1, A.N. Mohammed2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The bidirectional relationship between diabetes mellitus and periodontitis was obvious as both of them are considered chronic diseases. The risk of developing periodontitis was reported to be higher in diabetic patients specially with poorly control diabetes mellitus, which in turn can negatively impact glycemic control. Advanced glycation end-products have intertwined relationship with oxidative product; increased in advanced glycation end-products could lead to oxidative stress and vice versa. The aim of current study was to investigate the possibility of using serum levels of (AGEs) for identification of the periodontal pathological condition in periodontitis patients with and without diabetes. Method: Twenty healthy individuals (control group), 30 patients with severe chronic periodontitis and 30 poorly controlled diabetic patients with severe chronic periodontitis were included. Full mouth (plaque index PlI, gingival index GI, bleeding on probing BOP, probing pocket depth PPD, clinical attachment loss CAL) were recorded by periodontal probing and serum advanced glycation end-products concentration were assayed using enzyme linked immunosorbent assays. Results: A non-significant difference was reported in plaque index PlI, gingival index GI, bleeding on probing between diabetic and non-diabetic patients with chronic periodontitis, while probing pocket depth, clinical attachment loss revealed a significant difference between diabetic and non-diabetic patients. Advanced glycation end-products presented with highest level in diabetic group (26.92) followed by chronic periodontitis group (15.91) then the control group (6.60), however, the correlation was non-significant with periodontal parameters. Conclusions: It is possible to use serum advanced glycation end-products level in the early diagnosis of chronic periodontitis in patients with and without diabetes.